Shish [compact disc] (Knik Records, 2025)
Over the past decade, Portugal. The Man has established themselves as one of rock's most prized possessions and a live phenomenon, with over 1,600 shows under their belts and a storied reputation as festival favorites. Originally heralding from Alaska, the Portland-based band soared to new heights in 2017 with the release of their now RIAA certified-Platinum album, Woodstock. The album was marked by the astounding success of their infectious single, "Feel It Still," which earned the group a plethora of new accolades including a GRAMMY for "Best Pop Duo/Group Performance," a 7x RIAA Platinum certification, a record setting 20-week residency at #1 on alternative radio, and an inescapable presence on the Top 40 airwaves. Alongside the shine of their myriad of musical accomplishments lies the group's long-standing passion for social justice. In fact, this is precisely the intersection in which Portugal. The Man thrives; throughout their career, the band has consistently exemplified how to deeply commit to both artistry and activism.